MODERN METHODS OF RADIATION TREATMENT OF TUMORS OF THE HEAD AND NECK (REVIEW) - R. I. Absalyamov (Опухоли головы и шеи, 2015)
This article analyzes the current trends in radiation therapy of primary and recurrent, localized and locally advanced head and neck tumors. Address the use of radiation therapy as a stand-alone options, or in combination with surgery. Describe the characteristics and evaluate the use of the most modern methods.